Drought Forecasting, using Artificial Neural Network (ANN) and Predict Values of Drought Condition Derived using NDVI Data - Kumar Sharma, Rajesh; Rajput, Mayank; Sharma, Rahul (International Journal of Computer Sciences and Engineering, 2020)
This paper focuses on drought forecasting, using Artificial Neural Network (ANN) and predicts the values of drought condition derived using Remote Sensing data of Indore (M.P). We have used the NDVI data as input data of ANN model for drought forecasting, and determine Standard Vegetation Index (SNDVI). Artificial Neural networks operate on the principle of learning from a training set. There is a large variety of neural network models and learning procedures. Two classes of neural networks that are usually used for prediction applications are feed-forward networks and recurrent networks. They often train both of these networks using back-propagation algorithm.